Pengaruh Beban Berlebih Terhadap Umur Rencana Perkerasan Jalan (Studi Kasus Ruas Jalan Soekarno Hatta Palembang) - Indah Handayasari; Rizky Dwi Cahyani (Sekolah Tinggi Teknik - PLN, 2016)
Excess burden ( overloading ) is not only due to the excessive load vehicles but can also be caused by the increased volume of traffic . One of the roads that run into problems , namely excessive load Jalan Soekarno Hatta Palembang in South Sumatra . Based on the survey conducted obtained calculation of traffic volume on Jalan Soekarno Hatta - Jalan Tanjung Api - Api in 2015 amounted to 1705.35 smp / h while on the opposite lane of traffic volume amounted to 1826.5 smp / hour . In addition, at Jalan Soekarno Hatta require added thick layer ( overlay ) of 4.8 cm to 8.7 cm and the ideal load for the actual load with the rest of the life of the existing pavement structure can only support the weight of excess ( overloading ) for 2 years and 6 months from a design life of 20 years.